Evaluating Outside the Box: An Alternative Framework for Analysing Social Protection Programmes. (1st October 2013) - Devereux, Stephen; Roelen, Keetie; Béné, Christophe; Chopra, Deepta; Leavy, Jennifer; McGregor, J. Allister
Summary: The evidence base on social protection programmes is expanding rapidly, largely pointing towards their positive impacts. Most evaluations rely heavily on quantitative techniques and experimental methods to allow for attribution of impacts. In this paper, we argue that new ways of investigation and analysis are needed to expand and deepen the evidence base in support of improved design and implementation of social protection. Greater emphasis on qualitative research, mixed methods and participatory evaluation is crucial, given current evidence gaps about programme dynamics and impacts. This paper proposes a new evaluation framework that goes beyond conventional approaches, by highlighting relatively neglected aspects related to programme processes, social dynamics and feedback loops in programme evaluations.